Assessment Of Antiviral Usage, Barriers, And Strategies For Scaling Up Hepatitis C Treatment In Malaysia: A Mix Methodology Study - Chan, Huan Keat (2023)
Malaysia adopted three key strategies to pursue the global goal of hepatitis C elimination, namely applying compulsory licensing on a direct-acting antiviral (DAA), introducing a standard DAA-based treatment regimen (sofosbuvir and daclatasvir) and decentralizing hepatitis C care through primary healthcare centers. This three-phase study adopted both quantitative and qualitative methods, aiming to (i) assess changes in the treatment coverage of individuals with hepatitis C and the government spending on antivirals after applying compulsory licensing, (ii) evaluate clinical outcomes in treatment recipients of the standard regimen, and (iii) explore barriers and potential strategies to further scale up pharmacological treatment under the existing hepatitis C care decentralization model.